Influence of canopy pruning on light availability and grain yield of intercrops in white siris (Albizia procera)-based agrisilviculture system - NEWAJ, RAM; DHYANI, S K; SINGH, TRALOKI; NEEKHER, SHIKHA; BARONIA, CHHAVI (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 2006–08 at Jhansi to elucidate the influence of canopy pruning in white siris [Albizia procera (Roxb.) Benth.] on light interception and grain yield of intercrop. The experiment was conducted in randomized block design with three replications. Blackgram (Vigna mungo (L.) Hepper) - mustard (Brassica juncia L. Czern. and Coss.) crop sequence was taken as intercrop. The pruning of tree canopy was done with 3 pruning regimes namely 70% canopy pruning, 50% canopy pruning and control (unpruned tree). The results reveal that the growth of A. procera (dbh, height and canopy diameter) was significantly (P= 0.05) higher in control (unpruned trees) compared with 50% canopy pruning and 70% canopy pruning. Grain yield of blackgram was two times higher in 70% canopy pruning than the yield obtained with unpruned trees. Similarly the yield of mustard was three times higher in 70% canopy pruning than unpruned trees during both the years. The grain yield of intercrop under 50% canopy pruning was also significantly higher than unpruned trees. Light interception by intercrops was higher under 70% canopy pruning and lower with unpruned trees. The light interception increased with increasing distances from tree base. The grain yield of intercrops was linearly correlated with light interception.